Dog bite safety at work: An injury prevention perspective on reported occupational dog bites in the UK. (October 2019) - Owczarczak-Garstecka, Sara C.; Christley, Rob; Watkins, Francine; Yang, Huadong; Bishop, Beverley; Westgarth, Carri
Highlights: 80% of bites occurred during: mail delivery, vet/kennel work, human care provision. Different demographics and occupations were bitten in different circumstances. Bite risk was controlled mainly through administrative controls, like policies. Pre-bite remedial actions focused on euthanasia or restricting contact with a dog. During-bite remedial actions focused on reducing bite impact by muzzling dogs. Abstract: Dog bites affect the health and wellbeing of the victims and impact the organisations whose employees are injured. However, bites in the course of work or measures used by the employers to remedy them have not been previously explored. This study used the Health and Safety Executive's database (Reporting of Injuries, Diseases and Dangerous Occurrences Regulation) to understand: (1) The occupational and demographic characteristics of bite victims; (2) Circumstances in which they were bitten; and (3) The remedial actions listed by the employers. Between April 2011- March 2018, 1812 dog bites were reported; middle-age men were most often bitten demographic. Dog bites occurred in two distinct scenarios. Firstly, entering or leaving a private property, typically whilst delivering mail with a dog owner often present and the victim usually not interacting with or aware of the dog before the bite. In the second scenario, the victim was usually a female, dog professional, familiar with the dog and interacting with them before the bite. The remedial actions used by the employers focused on reducing the risk by acting pre- or during the bite event (e.g. euthanizing the offending dog, restricting dog access to employees or providing protective equipment). Post-event counter-measures were rare, but included counselling to the victims. Risk was addressed primarily through administrative measures (e.g. policies), which commonly targeted changing individuals' behaviour, which may limit effectiveness of prevention. Drawing on injury prevention models we suggest novel ways of preventing bites, e.g. equipment re-design and addressing social norms.